2021
DOI: 10.3390/cancers13205151
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocyte Polyploidy: Driver or Gatekeeper of Chronic Liver Diseases

Abstract: Polyploidy, also known as whole-genome amplification, is a condition in which the organism has more than two basic sets of chromosomes. Polyploidy frequently arises during tissue development and repair, and in age-associated diseases, such as cancer. Its consequences are diverse and clearly different between systems. The liver is a particularly fascinating organ in that it can adapt its ploidy to the physiological and pathological context. Polyploid hepatocytes are characterized in terms of the number of nucle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 132 publications
(216 reference statements)
0
18
0
Order By: Relevance
“…In addition, we included 24 normal fallopian tube (FT) samples, a spleen, and a kidney samples as negative controls. Normal liver samples were included as positive control tissues for CA, as the liver is the only organ in the human body that displays centrosome amplification in a healthy state [29][30][31] . An overview of all analysed tissue samples (n=318) is shown in Supplementary Table 1.…”
Section: Supernumerary Centrosomes Are Present In the Majority Of Hgs...mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, we included 24 normal fallopian tube (FT) samples, a spleen, and a kidney samples as negative controls. Normal liver samples were included as positive control tissues for CA, as the liver is the only organ in the human body that displays centrosome amplification in a healthy state [29][30][31] . An overview of all analysed tissue samples (n=318) is shown in Supplementary Table 1.…”
Section: Supernumerary Centrosomes Are Present In the Majority Of Hgs...mentioning
confidence: 99%
“…In addition to the 287 tumour samples, we also included 24 normal fallopian tube (FT) samples, one normal spleen, one normal kidney and five normal liver samples. Importantly, the liver is the only organ in the human body that displays centrosome amplification in a healthy state, likely caused by multi-nucleation and polyploidisation during tissue development [29][30][31] . Liver tissues were therefore used as positive controls in this study.…”
Section: Clinical Samples and Primary Tissue Processing And Selectionmentioning
confidence: 99%
“…Some latest studies have elegantly described the factors affecting cytokinesis and the molecular mechanism of cytokinesis failure, playing a guiding role in the subsequent research. Margall-Ducos et al 31,32 showed that cytokinesis is interrupted by impaired reorganization of the actin cytoskeleton at the division plane during the anaphase-telophase transition, resulting in loss of cell extension. Meanwhile, astral microtubules failed to contact the equatorial cortex and to deliver their molecular signal, which prevents activation of the RhoA pathway and leads to the generation of binucleate progenies.…”
Section: Dovepressmentioning
confidence: 99%
“…Although the mechanism underlying the regulation of the ploidy of hepatocytes and its effects on the pathophysiology of the liver are unclear, accumulating evidence indicates that polyploidy and alterations in the ploidy in hepatocytes influence liver homeostasis and diseases both positively and negatively. Whereas some reviews have outlined the advantages and disadvantages of polyploidy in health and disease in various organs [ 3 , 4 ], few papers have highlighted updated discussions about hepatocyte ploidy, especially ploidy alterations, and liver diseases [ 5 , 6 , 7 ]. This review discusses the significance of hepatocyte ploidy, with respect to physiological liver function, liver injury, and cancer.…”
Section: Introductionmentioning
confidence: 99%